老庄思想与时代意识观: The Perspective of Consciousness in Laozi and Zhuangzi's Philosophy and Contemporary Western Psychology - Jong Shin LIM, Kah Kean YAM, 林雍信，嚴家建 (Journal of Sinological Studies 漢學研究學刊, 2023)
Western psychology has reaffirmed the importance of consciousness and opened up a bridge for mutual exchange between Chinese and Western cultures. While drawing on the revaluation of the value of modern Western psychology, the thoughts of Laozi and Zhuangzi can also reflect the transcendence and diversity of Taoism in consciousness. The thoughts of Laozi and Zhuangzi established the philosophical thinking of the theory of cultivation and the concept of realm in the pre-Qin period. These theories are dominated by "Tao" and "Virtue". Western psychology lacks the exploration of the natural world and classifies it as a category of natural science. At the same time, it does not have a holistic understanding and realisation of "Tao", which has caused limitations and defects. Although transpersonal psychology has absorbed various new concepts of Eastern philosophy, it has not been properly integrated, mainly because the knowledge system of "understanding Tao" and "showing virtue" has not been perfected. This article believes that the thoughts of Laozi and Zhuangzi can make up for these defects.